Usulan Perbaikan Performansi Lini Produksi PT. XYZ - Trifenaus Prabu Hidayat; Adiyatma Adiyatma (Jurnal METRIS, 2014)
PT. XYZ is a company engaged in the field of packaging tissue with make- to-order system with four types ofproducts , namely toilet roll , napkin , handkerchief and facial tissue. On each work station of the fourthproduction line, occuring inefficiencies between workstations using a machine with manual work stations .Therefore, it is necessary to equity workload of each workstation and redesign of work stations that areexpected to minimize the amount of work in process . In this study, allocation of workstasion are made as aimprovement recommendation. Performance analysis conducted to see the efficiency of each of theseconditions . An increase in line efficiency of each production line. In this study, also conducted the analysisand design of work stations using software MannequinPro . Based on the proposed allocation of workstations , using software ProModel simulation to compare the value of WIP and utility with initial conditions.